Expanding Modern Methods Of Corporate Management In The Compliance Control System - Tojieva Maxliyo Jaxongir qizi (Genius Publishing Group, 2025)
One of the modern types of control over economic entities is compliance control, during which the compliance of corporations' activities with the current norms of Uzbek and international legislation is monitored. The article reveals the essence of compliance control, its main distinctive features and place in the general system of internal control of corporations. Compliance control is the foundation of control for any organization, a mandatory component of the management system, the most important part of which is the internal control system. The article discusses the measures to create and implement a compliance system in the business sector and in the industrial sectors of Uzbekistan. As well as the introduction of anti-corruption compliance in the activities of the Ministry of Justice of the Republic of Uzbekistan, Uzbekneftegaz JSC and Uzkimyoimpeks LLC
Keywords: corporation; compliance control; compliance risks